Direct Torque Control of Dual Three Phase Induction Motor fed by Direct Power Control Rectifier using Fuzzy Logic Speed Controller - Radhwane Sadouni; M’hamed Sahnoun; Ilyes Zababe; Hassen Reghioui (Science, Engineering and Technology)
This paper presents an advanced Direct Torque Control (DTC) approach for a Dual Three-Phase Induction Motor (DTPIM) powered by a Direct Power Control (DPC) rectifier. Traditional control methods, such as Proportional-Integral-Derivative (PID) controllers, often face performance issues when motor system parameters vary or exhibit non-linearity. To tackle these challenges, we propose a fuzzy logic-based speed controller for DTC, which enhances adaptability to system dynamics without necessitating a precise mathematical model. The fuzzy logic controller (FLC) is particularly effective in regulating speed under varying load conditions, improving robustness, and minimizing torque ripple. Furthermore, the DPC rectifier enhances power quality by reducing harmonic distortions, maintaining a stable DC link voltage, and improving the power factor. Simulation results obtained using MATLAB/Simulink software demonstrate that the combined DTC-DPC approach with fuzzy logic control delivers a superior dynamic response with minimal overshoot. This framework offers a promising solution for high-performance industrial applications that require precise torque control and stability under fluctuating loads while also supporting sustainable energy practices through improved power efficiency.